Politica Europeană de Vecinătate - Noi Iniţiative. Contribuţii ale României - Oana Mihaela Mocanu (European Institute of Romania, 2009)
– Due to the enlargement of the European Union towards the Central and Eastern Europe, the EU's external policy priorities have changed. Its frontier moving further to the East, it was necessary to adapt, and even reshape the institutional framework and the policies addressing its new immediate neighbourhood. In this context, a European Neighbourhood Policy (ENP) was put in place. Later on, the ENP consolidation and reform aims led to the setting up and promotion of new initiatives such as the Union for Mediterranean, the Eastern Partnership, which, together with the Black Sea Synergy project, intend to focus more upon the regional and multilateral dimension of the neighbourhood policy, being complementary to the bilateral basics of ENP. Romania has endorsed and continues to support the goal of a secure and stable area in its Eastern neighbourhood, mostly given its increased responsibilities derived from the Member State status at the Eastern border of the Union. An active supporter of the European perspective of the Republic of Moldova, and also a promoter of the regional and cross-border cooperation, Romania has set off a series of cooperation initiatives for the Black Sea area. It will be important to follow to what extent these projects will prove their efficiency in practical terms, especially in the new framework, generous in instruments, work mechanisms and actions, proposed by the European Neighbourhood Policy.
Keywords: 330; EU-Nachbarstaaten; Internationale Zusammenarbeit; Rumänien